Feasibility of conducting intradermal vaccination campaign with inactivated poliovirus vaccine using Tropis intradermal needle free injection system, Karachi, Pakistan. Issue 8 (August 2017) - Yousafzai, Mohammad Tahir; Saleem, Ali Faisal; Mach, Ondrej; Baig, Attaullah; Sutter, Roland W.; Zaidi, Anita K.M.
Abstract: Background: Administration of intradermal fractional dose of inactivated poliovirus vaccine (fIPV) has proven to be safe and immunogenic; however, its intradermal application using needle and syringe is technically difficult and requires trained personnel. Methods: We assessed feasibility of conducting an intradermal fIPV campaign in polio high risk neighborhood of Karachi using Tropis needle-free injector. During the one-day fIPV campaign, we measured average "application time" to administer fIPV with Tropis, collected ergonomic information and measured vaccine wastage. Results: Eleven vaccinator teams, after two-day training, immunized 582 children between 4 months and 5 years of age. Average "application time" ranged from 35–75 seconds; the "application time" decreased with the number of children vaccinated from 68 to 38 seconds between 1st and 30th child. 10/11 (91%) vaccinator teams found no ergonomic issues; 1/11 (9%) assessed that it was not easy to remove air bubbles when filling the device. There was 0% vaccine loss reported. No adverse events following immunizations were reported. Interpretation: We demonstrated that it is feasible, safe and efficient to use Tropis for the administration of fIPV in a campaign setting.